2018
DOI: 10.1002/erv.2629
|View full text |Cite
|
Sign up to set email alerts
|

Food addiction and other addictive behaviours in bariatric surgery candidates

Abstract: Clinical implications and potential limitations of the findings are discussed. Future studies should address the potential risk of postoperative addiction transfer using long-term follow-ups and controlled study designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 62 publications
6
24
1
1
Order By: Relevance
“…Convergent validity indices were also in line with previous studies using the YFAS 2.0 and mYFAS 2.0 symptom scores, with an association with binge eating and emotional eating severity, as well as a positive but moderate association with current and previous maximum BMI (this latter being observed only in the non-clinical population) (13,14,(20)(21)(22). We also replicated the reported positive association between the YFAS 2.0 symptom score and the level of psychological distress in bariatric surgery candidates (30).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Convergent validity indices were also in line with previous studies using the YFAS 2.0 and mYFAS 2.0 symptom scores, with an association with binge eating and emotional eating severity, as well as a positive but moderate association with current and previous maximum BMI (this latter being observed only in the non-clinical population) (13,14,(20)(21)(22). We also replicated the reported positive association between the YFAS 2.0 symptom score and the level of psychological distress in bariatric surgery candidates (30).…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the YFAS 2.0, previous studies conducted in people seeking treatment for obesity found an FA prevalence that ranged from 6.7 to 47.4% (18,30,56,57). These differences in FA prevalence might be explained by differences in terms of age (i.e., rates are higher in middle adulthood, followed by young adulthood, and lowest in elder adults), gender (i.e., greater among females), and sample type (greater among patients with an eating disorder) (23,24).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The prevalence of food addiction in the population with obesity is highly variable (from 7.7% to 47%), possibly depending on weight excess severity and clinical context, but seems to be consistently higher in females and older people [134][135][136]. According to an Italian cross-sectional study, food addiction, measured by the Yale Food Addiction scale (YFAS), was found in nearly 34% of patients seeking treatment for obesity, while a recent German cross-sectional study reported a 27% prevalence of food addiction in bariatric surgery candidates [137,138]. Another German cross-sectional study found a nonlinear correlation between food addiction and BMI, with food addiction being most prevalent in the underweight (15%) and obesity (17.2%) categories [139].…”
Section: A Motivational Contribution: Eating and Food Addictionmentioning
confidence: 99%